2022
DOI: 10.1371/journal.ppat.1010448
|View full text |Cite
|
Sign up to set email alerts
|

A newly emerging alphasatellite affects banana bunchy top virus replication, transcription, siRNA production and transmission by aphids

Abstract: Banana bunchy top virus (BBTV) is a six-component ssDNA virus (genus Babuvirus, family Nanoviridae) transmitted by aphids, infecting monocots (mainly species in the family Musaceae) and likely originating from South-East Asia where it is frequently associated with self-replicating alphasatellites. Illumina sequencing analysis of banana aphids and leaf samples from Africa revealed an alphasatellite that should be classified in a new genus, phylogenetically related to alphasatellites of nanoviruses infecting dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 87 publications
(135 reference statements)
2
35
0
Order By: Relevance
“…The BBTV is currently reported in Africa, Asia, and Australia, while the vector is present in all banana-growing regions, even where BBTV is not yet reported (CABI 2022a, 2022b). This virus belongs to the family Nanoviridae and the genus Babuvirus , with a capsid possessing multicomponent circular single-stranded DNA genomes encapsulated in small (18–20 nm) isometric particles (Burns et al 1995, Timchenko and Bernadi 2007, Stainton et al 2015, Mukwa et al 2016, Guyot et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The BBTV is currently reported in Africa, Asia, and Australia, while the vector is present in all banana-growing regions, even where BBTV is not yet reported (CABI 2022a, 2022b). This virus belongs to the family Nanoviridae and the genus Babuvirus , with a capsid possessing multicomponent circular single-stranded DNA genomes encapsulated in small (18–20 nm) isometric particles (Burns et al 1995, Timchenko and Bernadi 2007, Stainton et al 2015, Mukwa et al 2016, Guyot et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although no direct link has been established on how BBTV utilizes these host TFs via effectors, previous research shows that the association of betasatellites (βC1) with Tomato yellow leaf curl China virus (TYLCCNV) increased viral pathogenicity by binding to several transcription factors that regulate plant defense responses 95 . Recently, it was reported that a self-replicating alphasatellite associated with BBTV contributes to viral replication, transcription, siRNA synthesis, and transmission 96 . Thus, more research may be undertaken to determine if the BBTV-associated alphasatellite interacts with the host's TFs to enhance viral pathogenicity in banana.…”
Section: Rna-seq Reveals Putative Susceptibility Factors For Bbtd Pro...mentioning
confidence: 99%
“…Nanovirus alpha-satellites are not believed to contribute any function to the other genome components as they do not trans-replicate segments of the helper virus ( Timchenko et al. 1999 ); instead, they rely on it for encapsidation, movement, and transmission ( Guyot et al. 2022 ; Mansourpour et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the absence of DNA-N in a field isolate has been reported ( Fu et al. 2009 ), and symptoms were observed in two plants obtained under laboratory conditions, following aphid inoculation, where this segment remained undetected ( Guyot et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%